Heat Shock Proteins: Protection and Potential Biomarkers for Ischemic Injury of Cardiomyocytes After Surgery - Santos-Junior, Valfredo de Almeida (Braz J Cardiovasc Surg, 2018)
The heat shock proteins are endogenous proteins with the ability to act as molecular chaperones. Methods that provide cell protection by way of some damage can positively influence the results of surgery. The present review summarizes current knowledge concerning the cardioprotective role of the heat shock proteins as occurs in heart damage, including relevant information about the stresses that regulate the expression of these proteins and their potential role as biomarkers of heart disease.